What use is SoTL?: Using the Scholarship of Teaching and Learning to Develop a Curriculum for First Year University History Classes - Clark, Jennifer (Journal of University Teaching and Learning Practice, 2009)
Literature pertaining to the scholarship of teaching and learning (SoTL) is growing but there are few studies dealing with disciplinary differences. The SoTL relating to History is a recently emerging development. But what use is SoTL for History if it can not be translated into improving teaching practice? This paper examines the process of identifying current thinking in the specific SoTL of History, especially the teaching of historical thinking, and applying it to the development of a new history curriculum for first year students.